Perhitungan Kinerja Simpang tidak Bersinyal akibat Hambatan Samping (Studi Kasus Jalan Kampung Lalang Km 7,5) - Adil, Muhammad; Ardan, Melloukey (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Research aims to evaluate the performance of the unsignalized intersection at Jalan Kampung Lalang KM 7.5 using the PKJI 2014 method to understand the impact of side barriers on traffic efficiency and safety. The problem is focused on unsignalized intersections often become congestion points and sources of accidents due to the absence of clear and effective traffic arrangements. The analysis showed that the highest traffic volume occurred on Sunday with 2571.4 vehicles/hour. The intersection capacity value was recorded at 4146 skr/hr with a degree of saturation of 0.62. The traffic delay on the major road is 5.254 seconds/skr, while the delay on the minor road reaches 13.269 seconds/skr. The geometric delay of the intersection was recorded at 4.414 sec/skr, and the total delay of the intersection was 11.297 sec/skr. Queuing opportunities ranged from 16.044% to 33.575%. With a degree of saturation < 75, this intersection falls into service category C, which indicates that traffic flow is still stable even though drivers are restricted in their choice of speed.